Oil price shock in the US and the euro area - evidence from the shadow rate and the term premium - Martin Pažický (Review of Economic Perspectives, 2021)
The aim of this article is to investigate the consequences of oil price changes for the economy of the US and the euro area. Oil price transmission channel is assessed using Granger causalities and structural vector autoregressive (VAR) specifications (applying the Cholesky factorization and the restrictions following the method of Blanchard and Quah). The conventional oil price transmission channel is extended by a shadow policy rate and term premium, as the importance of both indicators has been growing rapidly in recent years. The results confirm that the oil price shock is not negligible in the aftermath of the Global Financial Crisis and in the subsequent period of monetary policy normalization. The findings are confirmed by the outcomes of the Bayesian VAR specification with sign restrictions. The consequences of changes in oil prices have significantly grown since the introduction of unconventional monetary instruments. The magnitude of the response of industrial production, price level and shadow interest rate to the oil price shock is strongest in the period corresponding to the unconventional monetary policy. In many cases, however, the reaction is short-lived. The conventional instrument (policy rate) in the euro area has still not been sufficient to stabilize the economy in the recent period of monetary policy normalization in the US.
Keywords: B23; E42; E52; E58; Q43; 330; oil price; unconventional monetary policy; VAR; shadow rate; term premium